A combinatorial optimization approach for multi-hazard design of building systems with suspended floor slabs under wind and seismic hazards. (15th April 2017) - Chulahwat, Akshat; Mahmoud, Hussam
Highlights: Dynamic formulations for suspended floor slab building subjected to wind and seismic hazards are developed. A new combinatorial optimization framework is developed and utilized to optimize the structural configurations. Performance objectives are introduced using weighting functions. A performance comparison is made against a conventional composite system. Enhanced performance of buildings can be achieved if the proposed system is used in medium to high-rise buildings. Abstract: The possibility of structures experiencing multiple hazards of different types during their service life has always been present. However, design of structures has primarily been geared towards addressing the most dominant hazard at the location of interest. In recent years, the design philosophy of structures has shifted towards a more holistic approach of addressing multiple hazards to ensure adequate performance under different loading scenarios. This requires the utilization of new structural systems and the development of effective optimization methods that can address multiple hazards. In this study, a suspended floor slab-isolated structure is utilized as an optimization test system subjected to wind and seismic demands. To perform the optimization a new combinatorial optimization approach is proposed, which is a combination of two methods – Nelder-Mead and Coevolutionary Matrix Adaptation Evolution Strategy (CMA-ES). The two algorithms are integrated simultaneously to optimize three key design variables of the suspended slab system and to obtain a family of optimal solutions that can accommodate varying level of participation of each hazard. In doing so, a set of alternatives is provided to the designer to accommodate wide variations and combinations in hazards intensities. The results of the study highlight the effectiveness of tuning the suspended slab system to meet the wind and seismic performance objectives. The system is seen to be more effective in case of taller structures than shorter structures. For taller structures, the system can be optimized to improve performance under both wind and seismic hazards without significant trade-off on individual hazard performance. Furthermore, the system is seen to be more sensitive to wind loading than earthquake loading.